Relationship of severity of coronary artery disease with fasting blood sugar and glycosylated hemoglobin - Saha, Avishek; Kuila, Madhumita; Sharma, Ranjan Kumar (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is one of the major risk factors for coronary artery disease (CAD). Accordingly, in this study, attempt is to be made to assess the association of severity of CAD by angiography with fasting blood sugar (FBS) and hemoglobin A1c (HbA1c). Aims and Objectives: To evaluate coronary angiographic abnormalities in patients of Diabetes. Materials and Methods: Six hundred adult patients of both sexes admitted in the department of cardiology, Nil Ratan Sircar Medical College and Hospital, Kolkata with ischemic heart disease from June 2018 to February 2020 underwent FBS and glycosylated Hb besides other routine tests. Coronary angiography done and the severity of CAD was assessed by SYNTAX SCORE was correlated. It is an observational, Cross-sectional hospital-based single center study. Results: Syntax scores were highest in the body mass index ≥30 kg/m2 group (16.5). Patients with Syntax score ≥33 are found to have much higher values of HbA1c (6.8±1.3) compared to those with Syntax score of ≤22 (6.4±1.8). Fasting blood glucose level in Syntax score ≥33 group has been found to be significantly higher compared to the group of Syntax score ≤22. Conclusion: Patients having DM and/or metabolic syndrome are found to have more severe form of CAD than those who don’t have either of these.